Determine the remainder when
is divided by .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
To simplify the problem, consider that by definition
n = ⌊ n ⌋ + { n }
Hence
S = i = 0 ∑ 2 0 1 5 ⌊ 2 5 2 i ⌋ = S 1 i = 0 ∑ 2 0 1 5 2 5 2 i − S 2 i = 0 ∑ 2 0 1 5 { 2 5 2 i }
From the formula for a geometric series we get
S 1 = 2 5 2 2 0 1 6 − 1
For S 2 we'll see how 2 i behaves when considered m o d 2 5
i 0 1 2 3 4 5 6 7 8 9 1 0 2 i m o d 2 5 1 2 4 8 1 6 7 1 4 3 6 1 2 2 4
o r d 2 5 ( 2 ) ∣ ϕ ( 2 5 ) , or o r d 2 5 ( 2 ) ∣ 2 0 and we can see that o r d 2 5 ( 2 ) > 1 0 so it must be 2 0 . Hence 2 is a primitive root modulo 2 5 and it generates ( Z / 2 5 Z ) ∗ .
With this we can calculate S 2 , since if
2 j ≡ k m o d 2 5 0 < k < 2 5
Then
{ 2 5 2 j } = { 2 5 2 5 m + k } = 2 5 k
So S 2 can be subdivided in groups of 2 0 addends whose sum is
2 5 x ∈ ( Z / 2 5 Z ) ∗ ∑ x = 1 0
There are ⌊ 2 0 2 0 1 6 ⌋ = 1 0 0 such groups
The last 1 6 addends add up to 2 5 1 8 5
Hence
S 2 = 1 0 ⋅ 1 0 0 0 + 2 5 1 8 5 = 2 5 2 5 1 8 5
Consequently
S = S 1 − S 2 = 2 5 2 2 0 1 6 − 2 5 1 8 6
We now need S m o d 1 0 0 , considering m o d 4 and m o d 2 5 separately
S ≡ 2 2 0 1 6 − 2 5 1 8 6 ≡ 2 m o d 4
Consider the numerator of the fraction m o d 6 2 5
ϕ ( 6 2 5 ) = 5 0 0 ⟹ 2 2 0 1 6 ≡ 2 1 6 m o d 6 2 5
2 1 6 − 2 5 1 8 6 ≡ 6 5 5 3 6 − 1 8 6 ≡ 5 3 6 − 1 8 6 ≡ 3 5 0 m o d 6 2 5
This is equivalent to
2 5 S = 6 2 5 n + 3 5 0 ⟹ S = 2 5 n + 1 4
So
{ S ≡ 2 m o d 4 S ≡ 1 4 m o d 2 5
And from CRT this implies that S ≡ 1 4 m o d 1 0 0